High-performance photonic transformers for DC voltage conversion - Bo Zhao (Nature Portfolio, 2021)
Conventional DC-DC converters rely on switching operations and energy storing components which face both noise and scaling difficulties. Here, the authors present an alternative design for a DC-to-DC converter based on closely coupled LEDs and photovoltaic cells, which exhibits high efficiency, low noise, and miniaturizability.